Technical documentation and process - Whitaker, Jerry C. (CRC Press, 2013)
"Written for engineering professionals and students, this book discusses the importance of documentation and process development in large and small organizations. It offers practical guidelines and templates that can be adapted to a wide variety of organizations to assist the reader in adapting techniques that have worked successfully in other companies. It gives readers a starting point for moving forward on their own by using practical, proven templates and guides, allowing the reader to design a documentation process for their own organization. A menu of options and suggestions is provided to help readers develop documentation that meets specific needs"--